Rectal Buttonhole Tear Following Operative Vaginal Delivery - Atiyeh Vatanchi; Leila Pourali; Asieh Maleki; Maede Khosravi; Shima Hatami (Mashhad University of Medical Sciences, 2022)
Background & aim: A rectal buttonhole tear during childbirth is an isolated laceration of rectal mucosa and vagina without involvement of anal sphincter that its management is challenging in obstetrics. The aim of this study was to report a case of rectal buttonhole tear following operative vaginal delivery.Case report: A 31-year-old primigravid woman was admitted to the Maternity ward of a teaching hospital of Mashhad University of Medical Sciences for pregnancy termination. The patient underwent an induction of labor. She had a successful assisted vaginal delivery with vacuum. A Rectal buttonhole tear was found in in the rectovaginal septum, which was repaired immediately after delivery in operation room. Six weeks' follow-up visit showed a completely cured laceration and the patient reported no complaints of fecal incontinence or foul discharge.Conclusion: Rectal examination before and after suturing perineal tears following vacuum extraction can help the diagnosis of isolated laceration. Accurate evaluation and using the optimal surgical techniques are the main points to achieve the best results.